CONTRIBUTIONS ON OPTIMIZING THE LEARNING OF SPECIFIC CONTENTS OF THE VIth GRADE HANDBALL GAME - Ursachi Ionel; Leuciuc Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
In the physical education class, handball appears as a sports game, being practiced by both girls and boys, its popularity being equal among students. Due to the fact that it is an accessible game, regarding the materials and work surface, handball is one of the most popular sports games used by teachers, in their teaching, in physical education lessons. The hypothesis underlying this paper is that one can optimize the means of teaching the handball game, as well as learning new technical-tactical elements in the sixth grade, if new and dynamic teaching methods are used, which will be attractive for students. In order to obtain favorable results for the process of learning and strengthening the motor skills specific to a sports game, it is necessary that the training should be carried out constantly and continuously, without too many interruptions. From this point of view I can say that there are setbacks in the case of schools, especially in rural areas, due to the lack of sports base. Being played only when the weather conditions are favorable, there are quite long breaks in the teaching process. These lead to losses, of a motor nature (forget certain elements) and of a temporal nature (time is lost from the following period because it is necessary to insist on regaining lost knowledge).